DEMAND FOR ORAL HEALTH CARE SERVICES AMONG WORKERS AT SEYANG CORPORATION VIETNAM (Vietnam Journal of Community Medicine, 2026)
Objective: To describe the demand for oral health care services among workers at Seyang Corporation Vietnam Co., Ltd. in 2023.Methods: A cross-sectional descriptive study was conducted among 273 workers at Seyang Corporation Vietnam Co., Ltd. from August to November 2023. Data were collected through structured face-to-face interviews combined with clinical oral examinations. Study variables included sociodemographic characteristics, oral health status, history of oral health care service utilization, treatment needs for common oral conditions, and ability to pay. Data were analyzed using SPSS version 16.0.Results: The majority of workers had oral health problems, with nearly half having not received treatment. Only 41.4% of workers had ever used oral health care services, mainly for curative procedures such as tooth extraction, scaling, dental fillings, and dentures. Most workers tended to delay treatment for gingivitis and dental caries until they could arrange time or until pain occurred. Treatment needs differed significantly by oral health status (p
Keywords: Workers; oral health care; treatment demand; dental services; occupational health.